Investigation of cirrus cloud properties in the tropical tropopause layer using high-altitude limb-scanning near-IR spectroscopy during NASA-ATTREX - S. F. Colosimo; N. Brockway; V. Natraj; R. Spurr; K. Pfeilsticker; L. Scalone; M. Spolaor; S. Woods; J. Stutz (Atmospheric Measurement Techniques, 2024)
Tropical-tropopause-layer cirrus clouds and their radiative effects represent a major uncertainty in the evaluation of Earth’s energy budget. High-altitude aircraft offer an opportunity to provide observations at cirrus cloud altitudes, most commonly using in situ measurements of ice particle optical properties and composition. In particular, remote sensing of scattering properties and near-IR ice water absorption in the limb can provide unique insights into thin and sub-visible cirrus clouds. Here we present novel spectroscopic observations of path-averaged ice water absorptions on board NASA’s Global Hawk aircraft during the Airborne Tropical TRopopause Experiment (ATTREX), which took place in 2011, 2013, and 2014. The University of California Los Angeles and University of Heidelberg mini-differential optical absorption spectroscopy (mini-DOAS) instrument provided multi-angle limb-scanning observations of scattered solar radiation in the near-IR (900–1726 nm), allowing the identification of ice and liquid water, O2, CO2, and H2O. The VLIDORT-QS radiative transfer (RT) code was specifically developed for this study and used to simulate high-altitude limb observations for varied cloud scenarios. We performed a comprehensive sensitivity study, developing a fundamental understanding of airborne near-IR limb observations of cirrus clouds. We identified two general distinct cases: a linear regime for optically thin clouds, where the ice absorption is proportional to ice water content (IWC), and a regime for optically thick cirrus clouds, where ice absorption is in saturation and independent of IWC. Results also demonstrate how molecular oxygen absorption can be used to infer information on optical properties of ice particles in the second regime only, with minimal information for thin cirrus clouds. We also explored the feasibility of retrieving IWC from mini-DOAS path-averaged ice water absorption (SIWP) measurements. This innovative interpolation-based approach requires a small number of RT calculations per observation to determine the sensitivity of SIWP to IWC. Spectral retrievals were applied for a particularly interesting case during Science Flight 2 over Guam in February 2014, during which the aircraft flew in circles in the same general area for an extended period of time. Retrieved IWC results are consistent with independent in situ measurements from other instruments on board. The measurements of ice particle scattering and absorption at different azimuths relative to the sun and at different altitudes represent a unique opportunity to test our approach and to infer properties of the ice particles, together with information on cirrus cloud radiative transfer.